Involutions on a Tropical Line - Roé, Joaquim (MATHEMATICA SCANDINAVICA, 2013)
Tropical involutive linear maps and pencils of degree 2 on the tropical projective line are introduced and studied. Both concepts are related in a similar way to linear involutions and $g^1_2$'s in the classical (algebraic) projective line, and tropicalization relates the algebraic phenomena to the tropical ones.